Characterisation and Solution Chemistry of N-Acetyl-Cobalt(III)-Microperoxidase 8 - Sannasy, Desigan (My University, 2007)
This dissertation describes the synthesis, physical characterisation and solution chemistry of NAc-CoIIIMP8, a biomimetic model compound of vitamin B12a, synthesised from the haemoctapeptide derived from horse heart cytochrome c. Peptic and tryptic digestion of horse heart cytochrome c removes much of the globular protein encapsulating the iron porphyrin prosthetic group. The resulting haemoctapeptide fragment retains residues 14 to 21 of the parent cytochrome (MP8) via thioether linkages to Cys-14 and Cys-17. Reductive demetalation of MP8 yielded the metal free MP8. This was treated with cobaltous acetate in an aerated aqueous solution to produce CoIIIMP8. CoIIIMP8 was acetylated by treatment with acetic anhydride and yielded N-acetyl-Co(III)- microperoxidase 8 (NAc-CoIIIMP8). It is well established that acetylation reduces aggregation of these haempeptides. The starting materials and products of each step during synthesis were characterised by UV-visible absorption spectroscopy, high performance liquid chromatography (HPLC) and fast atom bombardment-mass spectroscopy (FAB-MS). MP8 free base and Co(III)-MP8 were also analysed using luminescence spectroscopy. The molar extinction coefficients of NAcCoIII-MP8 in aqueous and ionic medium were determined using inductively coupled plasma-optical emission spectroscopy (ICP-OES) and UV- visible absorption spectroscopy. The extinction coefficient, e, of NAcCoIIIMP8 (? = 420 nm, pH 7.00, 25 ºC) in distilled water and 1.0 M NaClO 4 was 1.80 + 0.01 x 105 M-1 cm-1 and 1.66 + 0.01 x 105 M-1 cm-1, respectively. Beer’s law studies show that NAc-CoIIIMP8 remains monomeric in aqueous solution up to concentrations of at least 35 μM. The spectroscopic changes observed for NAc-CoIIIMP8 during the course of a spectrophotometric titration are very similar to those observed for NAc-FeIIIMP8, with both being consistent with six successive ionisations. By analogy with NAc-FeIIIMP8, we attributed the first (pK1 = 2.0 + 0.3) to the coordination of the c-terminal carboxylate group (Glu-21) of the appended polypeptide. The second acid range transition (pK2 = 2.8 + 0.1) for NAcCoIIIMP8 involved the deprotonation of the cationic His-18 and concomitant replacement of the c-terminal carboxylate by the neutral heterocyclic base. The third and fourth pKa’s are attributed to the ionisation of the haem propanoic acid groups (pK3 = 3.9 + 0.03) and (pK4 = 7.5 + 0.03). Ionisation of the cobalt-bound water molecule above neutal pH was assigned to pK5 = 9.2 + 0.04. Finally, we attributed pK6 (12.1 + 0.03) to the ionisation of the coordinated histidine trans to the OH- to form the histidinate complex (His--CoIII-OH-). A principal aim of this work was to demonstrate that the kinetics and the thermodynamics of the ligand substitution reactions of NAc-CoIIIMP8 can be studied spectrophotometrically; a comprehensive investigation of these reactions will be undertaken by othe rs. Towards this end the formation constants between NAc-CoIIIMP8 and N- methylimidazole and pyridine were determined. We observed the formation of a bis-substituted complex in the reaction of NAc-CoIIIMP8 with the ligands, but only mono-substitution with NAc-FeIIIMP8 and B12a. We attribute this first ligand binding to the replacement of the axial water molecule, and the second replacement of the axial histidine residue. The absence of the second reaction with NAc-FeIIIMP8 and B12a suggest that the CoIII-N(His) bond in NAc-CoIIIMP8 is significantly weaker than the FeIIIN( His) and CoIII-N(dimethylbenzimidazole) bond, respectively. When comparing the formation constants of NAc-FeIIIMP8, NAc-CoIIIMP8 and B12a, we found that the value of log K1 for NAc-CoIIIMP8 for these ligands is significantly higher than that reported for NAc-FeIIIMP8 and B12a. Kinetics studies of NAc-CoIIIMP8 with N-methylimidazole and methylamine were investigated. The data obtained did not follow conventional pseudo-first order kinetics; instead there was some evidence for biphasic kinetics. In the reaction of Nmethylimidazole with NAc-CoIIIMP8, we observed that the rate of reaction is virtually independent of the concentration of the incoming ligand. The results can be explained if the mechanism proceeds through a purely dissociative mechanism, i.e., if the rate of the reaction is controlled by the rate at which, firstly, the water molecule dissociates from the CoIII centre and, secondly, the histidine dissociates from the metal. The second order rate constant, k2, could not be determined since the rate of reaction is independent of Nmethylimidazole concentration. In the reaction of methylamine with NAc-CoIIIMP8, we observed that the rate of reaction is dependent on the concentration and participation of the incoming ligand. We propose that the displacement of water and histidine by methylamine involves an interchange mechanism (Id), where the bond forming and bond breaking occur simultaneously, and thus the rate of reaction becomes dependent on the concentration of the incoming ligand. The results showed that the rate of reaction for methylamine with NAc-CoIIIMP8 was faster than with N-methylimidazole. We attributed these differences in rate constants to the size of the incoming ligands. N-methylimidazole is a secondary amine and is relatively more bulky than methylamine which is a primary amine; therefore it is easier for methylamine to attach to the metal centre compared to N- methylimidazole. For comparison, the rate of reaction of B12a with N-methylimidazole and methylamine was determined. The results show that the rate of the reaction between NAc-CoIIIMP8 and B12a with N-methylimidazole and methylamine are significantly different. Furthermore, we observe only mono -substitution in B12a and bisubstitution in NAc- CoIIIMP8. Overall, the results presented in this work do give a general indication on how thermodynamically stable a CoIII ion is in a porphyrin ring and also to a very limited extent show that a porphyrin does not confer the same kinetic lability on the CoIII ion as the corrin ring.
Student Number : 0010064D - MSc dissertation - School of Chemistry - Faculty of Science
Keywords: Iron Porphyrins; microperoxidases; Cobalt Corrinoids; Vitamin B12; Cobalt-Porphyrins